Evaluation of stability failures of embankments on soft clays - Koirala, Naresh P.; Brand, E.W.; Balasubramaniam, A.S.; Holmberg, Soren; Government of the Netherlands (Bangkok : Asian Institute of Technology, 1977)
Fifty six published case histories of embankment failures on soft ground are compiled and reviewed. The embankments are classified into three different classes depending on the quality of the available data. A new term called 'critical depth' is defined, and it is shown that the circle with the minimum factor of safety lies between 0 & 2.5 m below the position of the minimum strength in a subsoil which exhibits a classical strength profile with a crust of high strength at the ground surface. A design factor of safety of 1.2 for Bangkok embankments is proposed. Two sets of design curves are developed, one for embankments on Bangkok soil and the other for embankments in other regions. The new design curves give better solutions for soils with low PI values, a range in which the Bjerrum curve failed. An alternative method of design of embankments by using the bearing capacity factor, Ne, is also proposed.
A thesis submitted in partial fulfillment of the requirements for the degree of Master of Engineering of the Asian Institute of Technology, Bangkok, Thailand
Thesis (M.Eng.) - Asian Institute of Technology, 1977
Keywords: Shear strength of soils; Embankments